Contrasting behaviors of pre-ozonation on ceramic membrane biofouling: Early stage vs late stage. (15th July 2022) - Jiang, Ting; Tian, Tian; Guan, Yan-Fang; Yu, Han-Qing
Highlights: Biofouling was aggravated at early-stage while alleviated at late-stage under pre-ozonation. Complexation of DNA with Al2 O3 surface aggravated biofouling at early stage. Pre-ozonation inhibited microbial growth and alleviated biofouling at late stage. Cake layers exhibited temporal and spatial differences in biofouling evolution. Abstract: Pre-ozonation coupled with ceramic membrane filtration has been widely used to alleviate membrane fouling. However, information on the efficiency and underlying mechanism of pre-ozonation in the evolution of ceramic membrane biofouling is limited. Herein, filtration experiments with a synthesis wastewater containing activated sludge were conducted in a cross-flow system to evaluate the effects of pre-ozonation on ceramic membrane biofouling. Results of flux tests show that pre-ozonation aggravated biofouling at the early stage, but alleviated the biofouling at the late stage. In situ FTIR spectra show that the aggravated biofouling with pre-ozonation was mainly caused by the enhanced complexation between phosphate group from DNA and Al2 O3 surface and the increased rigid of proteins' structure. At the early stage, more severe pore blockage further substantiated the higher permeate resistance. By contrast, more dead cells were observed on membrane surface at the late stage, indicating the prevention of biofouling development after long-term pre-ozonation. Additionally, the structures and compositions of cake layers at the early and late stages exhibited considerable differences accompanied by the variation in microbial community with the evolution of biofouling. Therefore, this work demonstrates the effectiveness of pre-ozonation in biofouling in long-term operation and provides mechanistic insights into the evolution of biofouling on ceramic membrane. Graphical abstract: Image, graphical abstract